Study of serum Ferritin and NT-proBNP levels in patients with heart failure - Doan, Chi Thang; Hansana, Phetchinda; Huynh, Van Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Objectives: To investigate serum ferritin levels in patients with heart failure and to assess the correlation of ferritin, NT-proBNP levels with heart failure severity and between NT-proBNP and ferritin. Methods: Cross - sectional description study on 101 patients diagnosed with heart failure and undergoing inpatient treatment at the Department of Internal Cardiology, Cardiovascular Center, Hue Central Hospital from 05/2022 to 08/2023. Results: The average age of the study sample was 70.0 ± 16.4 years. Females constitute a higher proportion with a female/male ratio = 1.7. NYHA III heart failure accounted for the highest rate (47.5%). In terms of ejection fraction, EF ≥50% accounted for the highest rate of 54.5%. As many as 93 patients (92.1%) had anemia in the study. The incidence of ferritin reduction in the NYHA I/II heart failure group (57.4%) was higher than in NYHA III/IV (55.6%). Regarding ferritin and ejection fraction, ferritin decreased in the group with reduced EF at a rate of 56.1%, higher than in the group with non-reduced EF at a rate of 43.9%, however the difference was not statistically significant (p > 0.05). Anemia patients with reduced ferritin had significantly higher levels of NT-proBNP (14271.97 ± 12810.17 pg/ml) than the anemia group with normal ferritin (8255.60 ± 11121.41 pg/ml), p < 0.05. NT-proBNP has a moderate positive correlation with ferritin (r = 0.422; p < 0.05), a moderate negative correlation with RBC (r = -0.465; p < 0.05), Hb (r = -0.352; p < 0.05), HCT (r = -0.408; p < 0.05) in patients with heart failure according to NYHA III/IV. Conclusions: Serum ferritin in patients with heart failure may be an indicator of iron deficiency. Our study shows that there is a positive correlation between NT-proBNP and ferritin in patients with severe heart failure.